2022
DOI: 10.1039/d1ra08235c
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the dimethyl ether carbonylation performance over hydrogen-type mordenites modified by pyrazole hydrochloride

Abstract: Hydrogen-type mordenite (HMOR) modified with pyrazole hydrochloride (Pya·HCl) was prepared by the ion exchange method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Alternatively, pyrazole is a smaller nitrogen-containing heterocyclic compound with a molecular diameter of 0.434 nm. It would be more difficult for it to pass through the 8 MR tunnel and easier for it to enter the 12 MR tunnel to shield the active sites of carbon deposits [20]. Moreover, weakly basic pyrazole reacts with hydrochloric acid to form an aqueous solution of pyrazole hydrochloride (Pya•HCl), which can achieve the same function of removing non-framework aluminum in HMOR as nitric acid [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, pyrazole is a smaller nitrogen-containing heterocyclic compound with a molecular diameter of 0.434 nm. It would be more difficult for it to pass through the 8 MR tunnel and easier for it to enter the 12 MR tunnel to shield the active sites of carbon deposits [20]. Moreover, weakly basic pyrazole reacts with hydrochloric acid to form an aqueous solution of pyrazole hydrochloride (Pya•HCl), which can achieve the same function of removing non-framework aluminum in HMOR as nitric acid [21].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, weakly basic pyrazole reacts with hydrochloric acid to form an aqueous solution of pyrazole hydrochloride (Pya•HCl), which can achieve the same function of removing non-framework aluminum in HMOR as nitric acid [21]. Liu et al [20] found that Pya•HCl could selectively enter 12 MR in the ion exchange process, and, in turn, the stability of the modified HMOR was improved. Tartaric acid is highly acidic, and its boiling point is as high as 399.3 • C, which is much higher than the reaction temperature of DME carbonylation.…”
Section: Introductionmentioning
confidence: 99%